Fire and climate in Mongolia (1532–2010 Common Era) - Amy E. Hessl; Peter Brown; Oyunsanaa Byambasuren; Shawn Cockrell; Caroline Leland; Ed Cook; Baatarbileg Nachin; Neil Pederson; Thomas Saladyga; Byambagerel Suran (Geophysical Research Letters)
Abstract Recent increases in wildland fire, warming temperatures, and land use change have coincided in many forested regions, making it difficult to parse causes of elevated fire activity. Here we use 20 multicentury fire scar chronologies (464 fire scar samples) from Mongolia to evaluate the role of climate forcing of fire in the context of livestock grazing and minimal fire suppression. We observe no change in fire return intervals post‐1900; however, since the 1500s, periods of drought are coincident with more fire and shorter fire return intervals. We observe same year and some antecedent year effects of drought on fire, a pattern typical of semiarid forests elsewhere. During the instrumental period, drought remains an important driver of fire; however, limited fire activity in recent decades may be due to the coincidence of drought and intensive grazing that have synergized to reduce fuel continuity and fire spread.